ESL teacher practices and perceptions of code-switching in a Malaysian Chinese independent school / Wong Yee Von - Wong, Yee Von (2019)
Code-switching has always been a common phenomenon in contemporary English classrooms in Malaysia. Preliminary observation on the utilisation of codeswitching has a distinctive attribute in Malaysian Chinese Independent School (MCIS). First, students are all Chinese medium background who at their primary levels had very little chance to use English. Such context is likely to encourage teachers to code-switch as Yao (2011) suggests, teachers are likely to use student's native language to engage with the students. Next, the MCIS community does not receive equal consideration to the national secondary school. Thus, comprehension of this setting is fractional, and the literature is restricted. In light of these, the present study provides analysis of English as a Second Language (ESL) teachers’ practices and perception of code-switching in an MCIS, Kuala Lumpur. The MCIS has been chosen on the basis of convenience. The study selected eight teachers, utilising purposive sampling. Ethnographic recording and a semistructured interview were used to gather the information. This study infers that there is a relationship between teacher practice and perspectives on the code-switch within the MCIS English classroom.